Determinação voltamétrica de aspartame e ciclamato de sódio em produtos dietéticos empregando um eletrodo de diamante dopado com boro - Medeiros, Roberta Antigo (2007)
The development of electroanalytical procedures for aspartame and sodium cyclamate determination in dietary products using a boron doped diamond (BDD) electrode and the square wave voltammetry (SWV) is reported in this work. The first procedure development is reported in related to the determination of aspartame in dietary products employing BDD electrode and the SWV technique after optimization of the experimental conditions. The recovery of aspartame from 8 samples ranged from 95.9 % to 104.4 % of the added amount. The analytical curve was linear in the aspartame concentration range from 9.9 x 10-6 mol L-1 to 5.2 x 10-5 mol L-1 with a detection limit of 2.3 x 10-7 mol L-1. The relative standard deviation for 5 successive determinations of 1.0 x 10-4 mol L-1 aspartame was 0.17 % and the relative standard deviation for 5 determinations of aspartame in different days was 2.8 %. The concentration of aspartame determined in several dietary products using the BDD electrode and those concentrations determined using a HPLC method are in close agreement (calculated t-values did not exceed the critical values at the 95 % confidence level) and within an acceptable range of error. In the sequence, the analytical determination of sodium cyclamate was studied by oxidation of this substance on BDD electrode employed the SWV. The analytical curve for sodium cyclamate was linear in the concentration range from 5.0 x 10-5 to 4.1 x 10-4 mol L-1 with a detection limit of 4.8 x 10-6 mol L-1. The relative standard deviation for five successive measurements was 1.1 % and the relative standard deviation for determinations of 3.0 x 10-3 mol L-1 sodium cyclamate in five different days was 2,4 %. The recoveries values from five samples ranged from 98.6 % to 106,0 % and the results found using the proposed method agreed at the 95% confidence level with those from a HPLC method. Finally, a procedure for simultaneous determination of aspartame and sodium cyclamate was developed, once the oxidation peak potentials of the aspartame and sodium cyclamate are 1.6 V and 1.9 V, respectively. The analytical curves were linear in the aspartame concentration range from 5.0 x 10-6 to 4.0 x 10-5 mol L-1, with detection limit of 3.5 x 10-7 mol L-1 and from 5.0 x 10-5 to 4.0 x 10-4 mol L-1, with detection limit of 4.5 x 10 -6 mol L-1 for sodium cyclamate. The simultaneous determination of these sweeteners in various dietary products was implemented with success.